EXERCISE TECHNIQUES FOR THE PIANO (World Bulletin of Social Sciences, 2022)
In this article, the technique of performing exercises on the piano and the principle of taking into account specific students are closely related to the method of developmental learning. The success of education depends on the comprehensibility of the material, the ability to set tasks and use similar methods to solve them, as well as the teacher takes into account not only the existing, the opportunity, but also the "scope of future development" of the student Thoughts on the relationship are obtained.
Keywords: Piano; instrument; technique; pedagogy; artistic performance